Melatonin Prevents Death of Neuroblastoma Cells Exposed to the Alzheimer Amyloid Peptide - Pappolla, Miguel A. (J Neurosci, 1997)
Studies from several laboratories have generated evidence suggesting that oxidative stress is involved in the pathogenesis of Alzheimer’s disease (AD). The finding that the amyloid β protein (Aβ) has neurotoxic properties and that such effects are, in part, mediated by free radicals has provided insights into mechanisms of cell death in AD and an avenue to explore new therapeutic approaches. In this study we demonstrate that melatonin, a pineal hormone with recently established antioxidant properties, is remarkably effective in preventing death of cultured neuroblastoma cells as well as oxidative damage and intracellular Ca(2+) increases induced by a cytotoxic fragment of Aβ. The effects of melatonin were extremely reproducible and corroborated by multiple quantitative methods, including cell viability studies by confocal laser microscopy, electron microscopy, and measurements of intracellular calcium levels. The importance of this finding is that, in contrast to conventional antioxidants, melatonin has a proposed physiological role in the aging process. Secretion levels of this hormone are decreased in aging and more severely reduced in AD. The reported phenomenon may be of therapeutic relevance in AD.